Detection of a Prethrombotic State in Patients with Hepatocellular Carcinoma, Using a Clot Waveform Analysis - Shunsuke Fukui MD; Hideo Wada MD, PhD; Kohei Ikeda MD; Mayu Kobayashi MD; Yasuaki Shimada MD; Yuuichi Nakazawa MD; Hiroki Mizutani MD; Yuhuko Ichikawa; Yuuki Nishiura MD; Isao Moritani MD, PhD; Yutaka Yamanaka MD; Hidekazu Inoue MD, PhD; et al. (Clinical and Applied Thrombosis/Hemostasis, 2024)
Background: Although hepatocellular carcinoma (HCC) is frequently associated with thrombosis, it is also associated with liver cirrhosis (LC) which causes hemostatic abnormalities. Therefore, hemostatic abnormalities in patients with HCC were examined using a clot waveform analysis (CWA). Methods: Hemostatic abnormalities in 88 samples from HCC patients, 48 samples from LC patients and 153 samples from patients with chronic liver diseases (CH) were examined using a CWA-activated partial thromboplastin time (APTT) and small amount of tissue factor induced FIX activation (sTF/FIXa) assay. Results: There were no significant differences in the peak time on CWA-APTT among HCC, LC, and CH, and the peak heights of CWA-APTT were significantly higher in HCC and CH than in HVs and LC. The peak heights of the CWA-sTF/FIXa were significantly higher in HCC than in LC. The peak times of the CWA-APTT were significantly longer in stages B, C, and D than in stage A or cases of response. In the receiver operating characteristic (ROC) curve, the fibrin formation height (FFH) of the CWA-APTT and CWA-sTF/FIXa showed the highest diagnostic ability for HCC and LC, respectively. Thrombosis was observed in 13 HCC patients, and arterial thrombosis and portal vein thrombosis were frequently associated with HCC without LC and HCC with LC, respectively. In ROC, the peak time×peak height of the first derivative on the CWA-sTF/FIXa showed the highest diagnostic ability for thrombosis. Conclusion: The CWA-APTT and CWA-sTF/FIXa can increase the evaluability of HCC including the association with LC and thrombotic complications.